Expression of the epidermodysplasia verruciformis-associated genes EVER1 and EVER2 is activated by exogenous DNA and inhibited by LMP1 oncoprotein from Epstein-Barr virus - Frecha, Cecilia Ariana (2015)
EVER1 and EVER2 are mutated in epidermodysplasia verruciformis patients, who are susceptible to human betapapillomavirus (HPV) infection. It is unknown whether their products control the infection of other viruses. Here, we show that the expression of both genes in B cells is activated immediately after Epstein-Barr virus (EBV) infection, whereas at later stages, it is strongly repressed via activation of the NF-κB signaling pathway by latent membrane protein 1 (LMP1). Ectopic expression of EVER1 impairs the ability of EBV to infect B cells.